(untitled) (Cardiovascular Journal, 2019)
Background: Ischemic heart disease (IHD) is a common cardiac disorder and significant cause of mortality and morbidity Worldwide. Dyslipidemia plays an important role in the pathogenesis of young MI as evidenced from different studies. This present descriptive study is designed to evaluate the pattern of dyslipidemia in young patients of Chittagong region, suffering from MI. Methods: 100 patients of young myocardial infarction diagnosed by clinical, biochemical and ECG criteria were included in the study. Fasting lipid profile was measured in the patients with age less than 40 years. Results: Among the patients 44% patient had hypertension, 15% were diabetic, 40% patients had history of smoking and 12% patient were obese. Change of socioeconomic status found to have an influence in lipid profile like low density lipoprotein (LDL), total cholesterol (TC) and triglyceride (TG) (p<0.05) but high density lipoprotein (HDL) had no change (p>0.05). LDL was changed in relation with nature of works. TG was significantly found higher in rural community and advanced age group (p<0.05). HDL level was found varied with gender and others were found insignificant. Conclusion: Varied lipid profile was found among the young victims of MI in Chittagong region. It might be concluded that control of blood lipid might lower the coronary events among young patients. Cardiovasc. j. 2019; 12(1): 30-32